A simulation-based decision support system to improve the resilience of the food supply chain. Issue 9 (2nd September 2021) - Tsiamas, Konstantinos; Rahimifard, Shahin
ABSTRACT: The rapid growth of population since 1950s has resulted in an enormous increase in demand for all kinds of manufactured goods. Manufacturing supply chains are becoming more sophisticated and complex, in particular within global food sector. At the same time, an increasing number of disruptions, ranging from those related to climate change and economic crisis as well as those associated with the socio-political turmoil and modern criminal activities such as cyber-attacks, are threatening the day-to-day operations. Although in the recent years, there have been significant advancements in supply chain management methods and tools, food manufacturers are still struggling to mitigate the possible impacts of these disruptions, leading to questions over the long-term resilience of their supply chains. This paper presents a novel framework for the improvement of food supply chain resilience and proposes a simulation-based decision support approach to aid the manufacturers to mitigate the impact of a range of unanticipated disruptions, specifically those related to climate change. The application of this framework has been demonstrated using activities of a dairy product manufacturer together with other main actors from its supply chain, namely the dairy farmers and wholesalers.